Reproductive Characteristics of the Selected Cocoa (Theobroma cacao L.) Clones after Regenerated from the Somatic Embryogenesis Culture - Entuni, Gibson; Nori, Hollena; Edward, Rebicca; Jaafar, Ahmad Kamil bin Mohammad (Trends in Sciences, 2021)
This study was conducted to evaluate the reproductive characteristics of 4 elite cocoa clones (MCBC1, PBC230, KKM22 and KKM4) propagated via somatic embryogenesis culture. From the findings, all clones have similar reproductive characteristics with clones from conventional grafted. However, only KKM4 clone from immature zygotic embryo culture produced the shortest staminode to style distance of 1.83 mm. This consequently influenced flower stability by reducing the efficiency of pollination by insects. It was found that this clone also has the highest number of flowers drop after anthesis (5 flowers) and lowest production of cherelle (5 cherelles). Further observation revealed that floral development from first bud visible (BBCH51) to flower anthesis (BBCH68) of all clones took around 31 days. These cocoa flowers which remained receptive soon after anthesis at 10 am (day-31) until the next day (day-32) suggesting 2 days’ period of receptivity. HIGHLIGHTS It is crucial to assess the presence of off-type characteristics in the reproductive organ structure such as the distance between staminode to style, period of reproductive cycle and stigmatic receptivity of cocoa clones regenerated from somatic embryogenesis The converging and parallel type of staminode to style distances are the ideal flower spatial arrangements for the optimal pollination in cocoa plant compared to splay type Only KKM4 clone propagated from immature zygotic embryo culture showed variation in the distance between staminode to style distance and this caused pollination failure by insect which then consequently caused minimum cherelle production All regenerated cocoa clones observed with typical period of the reproductive cycle and stigmatic receptivity GRAPHICAL ABSTRACT